Digital technology for anaphylaxis management impact on patient behaviour: A randomized clinical trial. Issue 5 (4th November 2020) - Sala‐Cunill, Anna; Luengo, Olga; Curran, Adrian; Moreno, Nuria; Labrador‐Horrillo, Moises; Guilarte, Mar; Gonzalez‐Medina, Mónica; Galvan‐Blasco, Paula; Cardona, Victoria
Abstract: Background: Epinephrine is the first‐line treatment for anaphylaxis. Patients at risk should always carry an epinephrine autoinjector (EAI). Several EAI gaps have been identified. We sought to evaluate satisfaction using a medical device (digital technology comprising an EAI smart case connected to a mobile APP) with functions that overcome most of the EAI limitations and to determine whether patient behaviour and anaphylaxis management improve with its use. Methods: This was a randomized, open‐label, crossover clinical trial in a tertiary hospital involving patients with history of anaphylaxis carrying an EAI. The study was conducted in two three‐month periods, one with and one without the medical device. The primary endpoint was satisfaction with the medical device. Usability, adherence, anxiety and anaphylaxis episodes were evaluated as secondary endpoints. Results: A total of 100 patients were included (mean age 38.1 years, 74% female), and 95 completed the trial. The satisfaction visual analogue scale (VAS) after using the medical device was higher than before its use (89.1 [95% CI, 60.2‐99.1] vs 56.3 [95% CI, 48.1‐81.4]; P < .0001). The adherence VAS improved from 59.7 (95% CI, 54.0‐65.3) to 88.6 (95% CI, 84.2‐92.9) ( P < .0001). Overall, 90% patients found the medical device easy to use. Patients' anxiety decreased from 52.2% to 29.3% ( P < .001). Seven episodes of anaphylaxis occurred during the study, all in patients without the medical device ( P = .025). Eighty‐eight per cent of patients felt more involved in the management of anaphylaxis when using the medical device. Conclusion: This is the first clinical trial evaluating digital technology for EAIs, showing a change of behaviour in patients at risk of anaphylaxis, increasing satisfaction, improving adherence, and reducing anxiety, with good usability. Abstract : The study evaluates a medical device for EAI (digital technology comprising an EAI smart case connected to a mobile APP). After using the medical device, satisfaction and adherence with the EAI increased significantly and anxiety decreased while carrying the medical device. Almost all patients felt more involved in anaphylaxis management when using the medical device. Abbreviations: EAI, epinephrine autoinjector; mo, months; APP, application